Clinical and dermoscopic evaluation of intralesional vitamin D3 in treatment of cutaneous warts: a placebo-controlled study - Eman S Abdel-Azim; Rasha T.A Abdel-Aziz; Maha H Ragaie; Eman A Mohamed (Wolters Kluwer Medknow Publications, 2020)
Background Viral warts are known for their persistence and recurrence, causing frustration to patients and treating physicians. Researchers recently proposed the hypothesis that intralesional vitamin D3 would be an effective treatment option for warts. Objective To assess the efficacy of intralesional injection of vitamin D3 in the treatment of cutaneous warts by clinical and dermoscopic evaluation. Patients and methods Sixty-two patients with single or multiple warts were randomized into two groups, groups I and II, who were treated with intralesional vitamin D3 and normal saline, respectively. Injections were performed every 2 weeks for a maximum of four sessions. All patients were followed up for 6 months. Results Complete cure was reported in 56.25% of patients treated by intralesional vitamin D3. No serious adverse effects or allergic reactions were reported. None of the healed wart recurred by the end of follow-up period. Conclusion Vitamin D3 is an effective and safe treatment option in treating cutaneous warts. The use of dermoscopy adds a great value in evaluating treatment response and in decreasing the incidence of recurrence.